Challenges for antisense oligonucleotide-based therapeutics, in particular for exon 51-skipping in Duchenne muscular dystrophy - Aoki, Y; Nagata, T; Shimizu, Y; Takeda, S (2011)
Duchenne muscular dystrophy (DMD) is a lethal muscle disorder characterized by mutations in the DMD gene. These mutations primarily disrupt the reading frame, leading to an absence of functional dystrophin protein. Exon-skipping through the use of antisense oligonucleotides has served as a promising therapeutic approach for DMD, and clinical trials in DMD patients are currently underway. Recently, stable and less-toxic antisense oligonucleotides have been developed with a higher efficacy in mouse and dog models of DMD. Despite these advancements, this therapeutic approach is limited by relatively poor systemic delivery of antisense oligonucleotides to muscle, as well as toxicity effects. This review highlights the challenges for antisense oligonucleotide-based therapeutics for DMD, in particular with methods using exon 51-skipping. © 2011 IEEE.